Surgical resection of a giant retroperitoneal dedifferentiated liposarcoma: a case report - Zhong, Shijie; Yang, Wei; Li, Zhangchao; Li, Ruixue; Fu, Bimang (Frontiers in Surgery, 2025)
BackgroundLiposarcoma (LPS) is a rare mesenchymal soft tissue sarcoma, and dedifferentiated liposarcoma (DDLPS) represents a clinically significant and aggressive subtype. Retroperitoneal DDLPS poses significant clinical challenges due to its insidious onset, large tumor size at the time of diagnosis, complex anatomical relationships, and high rates of recurrence and multi-organ involvement.Case presentationWe present the case of a 64-year-old male who presented with a progressively enlarging abdominal mass, fatigue, and reduced appetite persisting for over five years. Imaging studies and interdisciplinary evaluation revealed a massive retroperitoneal tumor with invasion into multiple adjacent organs. The patient underwent comprehensive surgical resection involving the tumor, left kidney, spleen, and distal pancreas, along with diaphragmatic repair. Histopathological analysis confirmed high-grade dedifferentiated liposarcoma. Postoperatively, the patient developed mild complications, including pneumothorax, which were effectively managed. Postoperative imaging and laboratory examinations demonstrated that the tumor was completely resected, with the majority of organ functions effectively preserved.ConclusionThis case highlights the complexity of treating a large and multi-organ-involving retroperitoneal dedifferentiated liposarcoma. Radical surgical resection remains the most effective treatment approach, but while achieving complete resection, it is also necessary to take into account the maximum protection of the patient's vital organ functions.